(untitled) (Archives of Criminology, 1982)
In the present study the changes in behavior of young adult drug addicts are described, which occurred as their dependence has developed since the beginning of taking drugs. We regard as scientifically fruitless frequent general statements concerning young adult (as well as adult) drug addicts irrespective of their age and the stage of dependence. The research on which the present study is based was a part of multidisciplinary studies of young adult drug addicts which were conducted by the Department of Mental Health of the Polish Academy of Sciences in Łódź in the years 1974-76. It concerned all patients aged 15-23 registered in the out-patient clinics for young drug addicts and in district out-patient clinics for adults in the city of Łódź because of the repeated taking of narcotic drugs. It is important to note that the discussed population consisted of 102 young adults, of which 23% were girls. Three detailed interviews were carried on in relation to each case: one with the mother of the given boy or girl (in exceptional cases with another adult member of the family), the second one at school with the tutor and the teachers, and the third one with the drug addict himself . The questionnaires on which the interviews were based took into account, to a high degree, the family conditions of the addicts, their behavior at home , from their earliest childhood up to the latest months, their school history, ways of spending their leisure time, the outset and circumstances of taking drugs, the use of alcohol, the peer groups, living problems in the period preceding the taking of drugs and in subsequent years, delinquency etc. Data were also collected concerning the criminal records of the addicts and the history of various diseases treated in different out-patient clinics. The study was conducted by a team of several persons working under supervision of the author of the present paper. Estimation of the degree of dependence was based on medical diagnosis. Among the addicts, the following three stages of dependence were distinguished: the stage of social dependence, that of mental dependence and the stage of physical dependence. The greatest part (50%) of the addicts were in the stage of mental dependence. The addicts were noticed to move to the more advanced stages of dependence in course of time. The mean duration of the period of taking drugs was: with young adults socially dependent 5 months, with those mentally dependent 1 year 5 months, and with those physically dependent 2 years 8 months. There are, however, limitations to this regularity. Some individuals withdrew from talking drugs within the first 12 months of social dependence. Others reached the stage of mental dependence very rapidly, so to say cutting down or even skipping the first stage of dependence. There were also those who remained for a long time in the preliminary stage of the illness, that is, that of mental dependence, revealing no symptoms of physical dependence even after one or two years. It is thus apparent that the progress of dependence and its rapidity are not the derivative of the length of the period of taking drugs only. An important role is also played by the intensity of taking drugs, by their peculiarities and by the individual immunity of the central nervous system of a given person. The notion of the so-called social dependence is controversial to a certain degree and as such used only by some of the authors. However, the results of the present study speak in its favor as the term defining the first, and so to say preliminary stage of dependence, preceding the next stages of dependence in the medical sense. In the present study the notion of social dependence is of a very broad range, i.e., its criteria are not limited to the pressure of the peer group and the boy’s or girl’s eagerness to adjust themselves to this group. On the basis of the collected material, we included in the notion social dependence also the cases in which the addicts communicated with loose society circles, e.g. in cafés, which was accompanied by the predominant trend to adjust themselves to the fashion and customs of such circles, as well as the cases of an influence of individual persons of different sex attracted to each other. The notion of social dependence is worthy of separation, particularly, as the patterns of taking drugs have now become generally accepted among the youth. Taking certain drugs several times, or even once, caused a considerable improvement of mood of the individuals inclined to experience conflicts intensely, who had a low tolerance to frustration and a poor ability to overcome obstacles, if they only happened upon the drug which changed their mental stale favourably from their point of view. Phenmetrazine was good for some of the persons examined to suppress their mental inhibitions, while others used sedatives to suppress states of tension and excitement, still others - morphine and its derivatives to experience something new and to get away from the dullness of the everyday life. The process of social dependence turning into mental dependence among the addicts consisted in the fact that - as they were experimenting with various drugs in the company of others - they soon found that not only the interpersonal ties were hereby fortified, but also their hitherto only poorly tolerated mental state could undergo a favorable change. As this belief grew stronger and proved true in all next instances of taking the drug, they experienced the more and more intense desire to take such drugs whenever the state of tension, discouragement or irritation had reached a considerable degree of intensity. However, after some time the hitherto felt desires were dominated by additional and extremely trying sensations of not only mental but also physical nature which occurred in the periods of the break in drug taking. The addicts tried at any price to get rid of withdrawal symptoms. Most frequent were the complaints about the sensation of irritation, restlessness, inability to concentrate on anything, lack of energy, anxiety, insomnia or nightmares, headache and melalgia, hand tremor and other annoying and exhausting symptoms. The examined persons with these symptoms had already found themselves in the stage of physical dependence. In the diversity and variability of drugs taken by the addicts as their dependence developed, a following essential regularity could be noticed: the comparatively greatest diversity of drugs taken was usually found at the stage of social dependence. In that of mental dependence, morphine and the specimens approximal to it more and more prevailed among the drugs taken by a given individual, thus reducing the role of other drugs. The transition to physical dependence meant further concentration on the opiates (mainly morphine), while other drugs – including alcohol- became substitutes and were taken when the individual did not possess the favorite drug and thus felt withdrawal symptoms. The danger of conversion to morphine and other opiates, with all its consequences, thus grew as the taking of drugs continued. It is a matter of course that, as the individual gradually needed drugs more and more difficult to obtain (that, is, those from the morphine group), which were sold at a higher price, and as he needed more and more of the drug and found it more and more difficult to do without - the ways of obtaining it had to change. A phenomenon occurs which can be called escalation not only of the drugs taken, but also of the means of obtaining them. The means in question become more and more ruthless, one counts less and less both with one’s own hitherto existing line of conduct and ambitions and with the probable reactions of the environment. The means of obtaining drugs grow also more and more absorbing, they engage more and more time and efforts. Simultaneously followed the process of diminution of individual interests and of the disappearance of ambitions in the addicts. It was more and more difficult for them to acquit themselves of the hitherto performed social roles. And thus, for instance, within the range of the role of a pupil, the following symptoms could be found among the addicts beginning from the stage of mental dependence: considerable difficulties of concentration, the slowing down of the run of thought, passiveness and drowsiness during the classes, increasing absence from school, being far away with thought even if physically present at school, regular remiss in doing homework, indifference to school failures, reluctance to undertake efforts to overcome them - that is, greater and greater slackness in the school duties. School, usually quitted in the advanced stages of dependence, gave place to irregular and chance periods of working, which did not in the least lead to any professional promotion of a given individual. All the hitherto existing forms of activity which satisfied their former interests and life plans were - as the dependence developed - replaced by the efforts to obtain every now and again new doses of the longed-for drug. Parallel to this process new specific elements appeared in the life of the addicts: contacts with out-patient clinics, stays in detoxication centres and mental hospitals, which repeated from time to time, and in a considerable number of the cases – court appearances ending more than once with imprisonment. In general, it must be stated that the progress of dependence has led to intense degradation changes in the lives of the addicts. The whole of those changes were composed of the following: increasing problems and failure at school, quitting school, aggravating conflicts at home, participation in youth groups and circles out of control which were characterized by socially negative patterns of behavior, giving up one’s professional ambitions, staying for months in hospitals, undergoing detoxication treatment, gradual limitation of one’s aims and interests to obtaining and taking drugs, court appearances every now and again.